Light–Driven, Proton–Controlled, Catalytic Aerobic C–H Oxidation Mediated by a Mn(III) Porphyrinoid Complex - Neu, Heather M. (J Am Chem Soc, 2015)
The visible light-driven, catalytic aerobic oxidation of benzylic C-H bonds was mediated by an Mn(III) corrolazine complex. To achieve catalytic turnovers, a strict selective requirement for the addition of protons was established. The resting state of the catalyst was unambiguously characterized by X–ray diffraction as [Mn(III)(H(2)O)(TBP(8)Cz(H))](+), in which a single, remote site on the ligand is protonated. If two remote sites are protonated, however, reactivity with O(2) is shut down. Spectroscopic methods revealed that the related Mn(V)(O) complex is also protonated at the same remote site at −60 °C, but undergoes valence tautomerization upon warming.